Perfect and Perfective in Hausa - Mahamane, L. Abdoulaye (Afrikanistik online, 2008)
In West African languages that have the relative TAM marking, i.e., a system of syntactically conditioned alternating TAM paradigms, it is generally considered that the paradigms in each alternating pair have necessarily the same meaning. This paper shows that in Hausa, the Completive, which appears in pragmatically neutral clauses, and the Relative Perfective, which appears in pragmatically marked clauses (such as relative clauses), have, respectively, a basic perfect and perfective semantics, and that in some marked cases the alternation is not possible. The paper also shows that the two paradigms have acquired derived uses in a way consistent with the results of typological studies in the domain of tense/aspect.
Keywords: Aspekt; Hausa; TAM; Tempus; aspect; tense